Pengaruh Kepemimpinan, Motivasi Dan Lingkungan Kerja Terhadap Kepuasan Kerja Tenaga Kependidikan Pada Universitas Balikpapan - Dinda dita Rahayu; Didik Hadiyatno; Rahajeng Cahyaning Putri Cipto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to determine the influence of leadership, motivation, and work environment on the job satisfaction of educational staff at the University of Balikpapan. This research uses a quantitative approach. The analysis tool employed is multiple linear regression, processed using SmartPLS software. The sampling technique used is census sampling with a total of 72 respondents from the university's educational staff. Data were collected through observation, interviews, and questionnaires.The results of this study indicate that the leadership variable has a partial influence on the job satisfaction of educational staff at the University of Balikpapan. The motivation variable also has a partial influence on job satisfaction. However, the work environment variable does not have a partial influence on the job satisfaction of educational staff at the University of Balikpapan.